Heart of the Congo a Moira Productions film in association with Dateline Productions ; written, directed, narrated & produced by Tom Weidlinger ; Lillian Lincoln Foundation. - Weidlinger, Tom. ([distributed by] Bullfrog Films, 2004)
Amid threats of violence, corruption, and a legacy of colonial dependency, aid workers in the Congo help refugees who have lost everything. They seek to strengthen villagers' will, essential for a self-sufficient future. Heart of the Congo is a film about courage, perseverance and ways in which humanitarian aid makes a lasting difference.